Curation through use: Understanding the personal value of social media - Zhao, Xuan; Lindley, Siân (Proceedings of the 2014 SIGCHI conference on Human Factors in computing systems (CHI 2014), 2014)
Content generation on social network sites has been considered mainly from the perspective of individuals interacting with social network contacts. Yet research has also pointed to the potential for social media to become a meaningful personal archive over time. The aim of this paper is to consider how social media, over time and across sites, forms part of the wider digital archiving space for individuals. Our findings, from a qualitative study of 14 social media users, highlight how although some sites are more associated with ‘keepable’ social media than others, even those are not seen as archives in the usual sense of the word. We show how this perception is bound up with five contradictions, which center on social media as curated, as a reliable repository of meaningful content, as readily encountered and as having the potential to present content as a compelling narrative. We conclude by highlighting opportunities for design relating to curation through use and what this implies for personal digital archives, which are known to present difficulties in terms of curation and re-finding.